Hi Morgan82!

No, thats not true.

point has the coordinates (t,y), then the equation is

y = a + t*x

There are two points (-2,5) and (4,3), this leads to

5 = a+(-2)x

e.g.

5 = a - 2x (eq 1)

3 = a + 4*x (eq 2)

and now you need to solve the equations, like this

(eq1) - (eq2)

5-3 = a -2x - (a +4x)

2 = a -2x - a - 4x

2 = -6x

x = -1/3

Now you know x and substitute it in eq 1 (substitute in eq 2 would work, too)

5 = a - 2*(-1/3) (x=-1/3 in eq 1)

5 = a + 2/3

5 - 2/3 = 13/3 = a

So the solution is y = 13/3 -1/3*x

Do you understand?

Yours

Rapha